Usefulness of C-Reactive Protein and Clinical Characteristics in Identifying Severe Bacterial Infection in Children with Fever without Source (2022)
ABSTRACT: Objective: Fever continues to be the most frequent cause of care in the pediatric population. The uses of invasive and unnecessary tests result in discomfort to the patients. Local epide miological data could help to refine screening strategies, especially in low resources settings. The present study aims to describe the prevalence of serious bacterial infections in infants with fever without source and to evaluate the usefulness of clinical and laboratory parameters in the identification of serious bacterial infections. Materials and Methods: We included all children aged 0-36 months presenting with fever without source between January 2015 and December 2017. Demographic and clinical charac teristics, investigations, and management procedures were recorded at the time of inclusion. Potential predictors of serious bacterial infections were compared between patients with and without serious bacterial infections. Results: In total, 137 patients were included. Serious bacterial infections were diagnosed in 41 patients (29.9%; 95% CI, 22%-38%). The most frequent diagnosis in serious bacterial infec tion patients was urinary tract infection (78%). Serum C-reactive protein levels greater than 80 mg/L (odds ratio, 2.79 [1.14,6.86]) and total days with fever (odds ratio, 2.56 [1.81,3.62]) showed a significant association to predict serious bacterial infections. Conclusion: Most infants with fever without source presented self-limited febrile syndromes without evidence of severe bacterial infection. C-reactive protein levels greater than 80 mg/L and the number of previous days with fever were variables associated with the presence of serious bacterial infections. Our results need to be validated in other tropical countries.